KETELADANAN GURU EKONOMI PENGARUHNYA TERHADAP DISIPLIN SISWA KELAS XI DI SMA NEGERI 2 PEKANBARU - Wenty Febriyana; Gimin Gimin; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine whether there is a positive and significant influence of exemplary economics teachers on the discipline of class XI students at SMA Negeri 2 Pekanbaru. The population in this study were all class XI SMA Negeri 2 Pekanbaru as many as 87 students, thus taking the overall sample of the population, namely 87 students. Testing data using questionnaires and documentation. The data analysis used is simple linear regression analysis. The results of this study indicate that there is a positive and significant influence between the exemplary economy teachers on the discipline of class XI students at SMA Negeri 2 Pekanbaru with an influence contribution of 10.3% while the remaining 89.7% is explained by other factors not examined in this study.Key Words: Student Discipline, Teacher Exemplary